2019
DOI: 10.3389/fpsyg.2019.01273
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Role Distributions, Work Participation, and Stress Factors on Family Health-Related Outcomes: Study Protocol of the Prospective Multi-Method Cohort “Dresden Study on Parenting, Work, and Mental Health” (DREAM)

Abstract: The Dresden Study on Parenting, Work, and Mental Health (“ DR esdner Studie zu E lternschaft, A rbeit, und M entaler Gesundheit”, DREAM ) aims to prospectively investigate the relationship between parental work participation, role distribution, stress factors, and their effects on perinatal outcomes and long-term family mental and somatic health in a community sample targeting N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 179 publications
(176 reference statements)
1
42
0
Order By: Relevance
“…This investigation is part of the longitudinal cohort Dresden Study on Parenting, Work, and Mental Health (DREAM; DR esdner Studie zu E lternschaft, A rbeit und M entaler Gesundheit), which prospectively examines the relationship between parental work participation, role distribution, stress factors, and their effects on perinatal outcomes and long-term family mental and somatic health [ 42 ]. Expectant mothers and their partners were recruited during pregnancy predominately at information evenings in hospitals and birth preparation courses in and around Dresden, Germany.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This investigation is part of the longitudinal cohort Dresden Study on Parenting, Work, and Mental Health (DREAM; DR esdner Studie zu E lternschaft, A rbeit und M entaler Gesundheit), which prospectively examines the relationship between parental work participation, role distribution, stress factors, and their effects on perinatal outcomes and long-term family mental and somatic health [ 42 ]. Expectant mothers and their partners were recruited during pregnancy predominately at information evenings in hospitals and birth preparation courses in and around Dresden, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…Participants complete questionnaires covering a comprehensive field of physical and mental health outcomes. The measurement points encompass T1, during pregnancy, and five postpartum assessment waves: T2 at 8 weeks, T3 at 14 months, T4 at 2 years, T5 at 3 years and T6 at 4.5 years after birth, for a detailed description see Kress et al [42]. For the purpose of the present study, data from expectant mothers on working conditions during pregnancy (T1) and PPD symptoms at 8 weeks postpartum (T2) were analyzed.…”
Section: Study Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no studies were found that previously applied the WPC and the EPRES to the peripartum period. The present investigation is part of a large prospectivelongitudinal cohort study covering many elds of interest regarding employment, mental health, and associated factors (42). Therefore, it will be possible to incorporate further theoretical concepts and factors in future analyses.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In addition, no studies were found that applied the WPC and the EPRES to the peripartum period. The investigation is part of a large prospective-longitudinal cohort study covering many fields of interest regarding employment, mental health, and associated factors (42). Therefore, it will be possible to incorporate more theoretical concepts and factors in future analyses.…”
Section: Strenghts and Limitationsmentioning
confidence: 99%